(untitled) (Journal of Economics, Law and Society, 2025)
Writing and publishing on crowdfunding has been booming since it began in 2010, till it showed its first decline in 2020. Bibliometric analyses of crowdfunding literature are very few, and the existing ones did not investigate the decline, nor did they try to understand the direction it was taking. Using bibliometric network analysis on Scopus data from 2010-2024, we investigate whether this decline represents a natural evolution of scholarly attention or signals a paradigm shift in the field. Through the lens of Kuhn’s paradigm shift theory and citation lifecycle frameworks, we analyze co-authorship networks, citation patterns, and thematic evolution before and after 2020. Our findings reveal three distinct phases in crowdfunding research: emergence (2010-2015), consolidation (2016-2019), and transformation (2020-2024), with the latest phase characterized by greater fragmentation and a shift from financial mechanisms toward sustainability applications. This analysis provides critical insights for researchers, journal editors, and funding agencies navigating the evolving crowdfunding knowledge landscape. We also noted the underutilization of network science by researchers and have made some recommendations to remedy that in order to get better results in future analyses.